"All Things Are Lawful"? Paul’s Reframing of Freedom Through the Lens of Body (1 Corinthians 6:12-20) - LIANG, Yichen (中国基督教研究（ISSN：3068-479X）, 2025)
The relationship between the perception of human body and the understanding of freedom was a contentious issue in early Christian churches. This paper examines Paul’s reframing of freedom from the lens of the body in 1 Corinthians 6:12-20. Through a three-tiered methodology—social-historical analysis, rhetorical analysis, and exegetical study of the Corinthian texts—this paper first reconstructs the Corinthians’ theology of body and traces its intellectual roots in the dualistic view of body in Stoicism and the similar dualistic traits manifested in Proto-Gnosticism. I argue that Paul, using the rhetoric of diatribe, challenges this dualistic and individualistic view of body, rejecting its disembodied moral implications and articulating instead a holistic and communal vision of freedom grounded in the embodied participation within the body of Christ. Finally, by engaging in a dialogue between Paul’s reframing of freedom and the Confucian concept of freedom, this paper proposes a constructive hermeneutical bridge for interpreting Pauline concept of freedom in Chinese cultural contexts.